The Politics of Holocaust Representations on Film – From the Peaceful Landscape to the Death Gaze: Resnais, Lanzmann, and Farocki - Marija Ratković ([sic])
This paper explores the politics of Holocaust representations without dealing with the problem of the ethics of the representation itself, but rather indirectly: by asking what the strengths and limitations of film media representation are, it deals with the problem of the politic/politics of the Holocaust cinema. Furthermore, it looks at the heteronomies of a certain number of movies in relation to the autonomous field of art which also sets limitations of the media, especially by taking into account the dominant social contexts, politics, and the approved representational ethics. By applying the case study method to three documentary films – Night and Fog (1995) by Alain Resnais, Shoah (1985) by Claude Lanzmann, and Respite (2007) by Harun Farocki, what is being presented is the discrepancy between the concepts of politics and ethics of Holocaust representation. The chosen films represent three different points in time and three different dominant and avant-garde discourses of Holocaust representations. The author's thesis is not to deal primarily with the theme of the ethics of Holocaust representations, but to use the chosen films as case studies for representation of the politics and (de)construction of the memories of the Holocaust, which correlate with the dominant politics of the context that creates them. In that way, each interpretation of these films here is also a study of the dominant political discourse, and a study of the politics transgressing the discourse into the avant-garde practices of Holocaust representation suggested by these films.